Parametric Analysis of Wearable Vialess EBG Structures and Its Application for Low Profile Antennas - Adel Y.I. Ashyap; Zuhairiah Zainal Abidin; Samsul Haimi Dahlan; Huda A. Majid; Zuraidah Muhammad; Muhammad Ramlee Kamarudin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexElectromagnetic Bandgap (EBG) structures are one class of metamaterial with attractive properties that unavailable in nature and widely used for improving the electromagnetic performance. Its In-phase reflection frequency band is indicated as operation frequency band, whose characteristic is closely related to the parameters of EBG structure, such as patch width (w), gap width (g), substrate height (h) and substrate permittivity (ε). The presence of via within EBG structure is associated with design and fabrication complexities, which led the researchers to study uniplanar EBG. These structures require no via and can easily be fabricated and integrated with RF and microwaves application.  Therefore, an investigation study on the effect of the parameters of the vialess EBG surface and some design guidelines have been obtained. An example of an antenna integrated with EBG is also studied. The result indicates that the EBG ground plane significantly improves the work efficiency of the antenna in a particular frequency band.